A capability approach to examining the experiences and perceptions of Menstrual Hygiene Management (MHM) among homeless women in Cape Town - Mhlongo, Ayanda (Department of Social Development, 2021)
Homeless women face many challenges. They lack adequate housing and financial support and are confronted with the daunting challenge of securing sanitary products when menstruating (Parrillo and Feller, 2017). Menstruation is a crucial part of women's sexual and reproductive health (Reams, 2001). It is a significant biological experience that signifies a woman's transition from childhood to womanhood (Reams, 2001). For homeless women, purchasing menstrual products is an unreasonable financial burden (BRAWS, 2018). Homeless women end up using items such as rags, old socks, tissue paper, paper towels, torn pieces of clothing, or diapers to satisfy their menstrual needs (Mason et al., 2013). Often, homeless women go without menstrual protection altogether (Mason et al., 2013). This lack results in period poverty. Period poverty refers to a lack of sanitary products, menstrual hygiene education, toilets, hand-washing facilities, and/or waste management (Sanchez and Rodriguez, 2019). Period poverty manifests in the absence of Menstrual Hygiene Management (MHM). MHM is a term used to refer to menstruating females having absorbents to absorb or collect blood that can be changed in privacy as many times as required, having soap and water to wash the body, and having facilities to dispose the used menstrual management materials (Sommer and Sahin, 2013). The purpose of the research study was to qualitatively explore the experiences and perceptions of period poverty among homeless women in Cape Town (South Africa) using the capability approach. As a result, the study was guided by a qualitative research design. Nonprobability sampling was used in recruiting participants. In-depth interviews were conducted with 16 homeless women who experienced period poverty and received assistance from two organisations in Cape Town. The findings revealed that homeless women experience period poverty due to a lack of sanitary products and poor MHM. One of key challenges faced by the participants was that they do not have access to an adequate supply of water when having their period. Participants would then make use of dam, water under the bridge, public toilets or make use of a bucket in order keep clean during their period. This affected the confidence of the participants, making them feel inadequate. As a result, they developed unhealthy behaviours to survive the harsh realities of being homeless. This made them vulnerable to different forms of violence and affected their perception of the opportunities they believed they had access to. Based on the findings of this study, it is recommended that addressing period poverty amongst homeless women requires multifaceted policies and responses. Furthermore, there needs to be intense support from all stakeholders so that the issue of period poverty amongst homeless women is addressed as a wider public-health initiative. The financial burden of sanitary products should be eliminated across the globe. Essentially, free menstrual products should be made available to all menstruating individuals, including homeless women.